Dynamic performance simulation of hydraulic transmission for low speed vertical axis marine current turbine using MATLAB simulink - Souf-Aljen, Atef S. (2015)
For Malaysia, ocean energy can be the best resource of green marine renewable energy. This is for the reason, the generation of the electricity by burning of fossil fuels produces undesired greenhouse gases and moreover the reserves of fossil fuels are being depleted and there is no accurate way to determine how much still remains. Turbines using hydraulic drive are being used for generating electricity by some manufacturers in the wind industry as an alternative to gearbox drive-trains because of reliability issues. Likewise, in the marine renewable sector, hydraulic-drive is an attractive option in terms of improved system efficiency, reliability and robustness. This paper presents a time domain simulation of hydraulic transmissions for Low Speed Vertical Axis Marine Current Turbines (VACT) using MATLAB Simulink software. These turbines are applied to harness marine current energy because of their relative simplicity and represent a promising technology to exploit low speed currents due to their small plants with reduced installation and maintenance costs.